Continuing Education to Go: Capacity Building in Psychotherapies for Front-Line Mental Health Workers in Underserviced Communities. (June 2013) - Ravitz, Paula; Cooke, Robert G; Mitchell, Scott; Reeves, Scott; Teshima, John; Lokuge, Bhadra; Lawson, Andrea; McNaughton, Nancy; Skinner, Wayne; Cooper, Carolynne; Fefergrad, Mark; Zaretsky, Ari
Objective: To address the gaps between need and access, and between treatment guidelines and their implementation for mental illness, through capacity building of front-line health workers. Methods: Following a learning needs assessment, work-based continuing education courses in evidence-supported psychotherapies were developed for front-line workers in underserviced community settings. The 5-hour courses on the fundamentals of cognitive-behavioural therapy, interpersonal psychotherapy, motivational interviewing, and dialectical behaviour therapy each included videotaped captioned simulations, interactive lesson plans, and clinical practice behaviour reminders. Two courses, sequentially offered in 7 underserviced settings, were subjected to a mixed methods evaluation. Ninety-three nonmedical front-line workers enrolled in the program. Repeated measures analysis of variance was used to assess pre- and postintervention changes in knowledge and self-efficacy. Qualitative data from 5 se mi structured focus groups with 25 participants were also analyzed. Results: Significant pre- and postintervention changes in knowledge (P < 0.001) were found in course completers. Counselling self-efficacy improved in participants who took the first course offered (P = 0.001). Dropouts were much less frequent in peer-led, small-group learning than in a self-directed format. Qualitative analysis revealed improved confidence, morale, self-reported practice behaviour changes, and increased comfort in working with difficult clients. Conclusion: This work-based, multimodal, interactive, interprofessional curriculum for knowledge translation of psychotherapeutic techniques is feasible and helpful. A peer-led group format is preferred over self-directed learning. Its application can build capacity of front-line health workers in helping patients who suffer from common mental disorders.